Kajian Biomorphic Architecture dalam Perancangan Oceanarium Pekanbaru - Nurul Asyifa; Yohannes Firzal; Gun Faisal (ARSITEKTURA, 2020)
Pekanbaru is a city that is growing rapidly and becomes one of the cities that is frequently visited. But the tourist attraction by the city of Pekanbaru are still lacking. Besides that in the geographical triangle, the water region in Riau Province is bigger than the land area, so the water region in Riau Province has a very high potential. But education about marine life and conservation areas that support biota protection in Riau province is still very least. Therefore, we need a public facility that is equipped with recreational, educational, and conservational needs. To actualize these public facilities, then will be designed an Oceanarium in Pekanbaru City. Oceanarium is a reservoir in a giant aquarium for the conservation of plants and marine biota that serves as a means of education, research, preservation, marine development, and exhibited as a means of recreation. The theme of the Oceanarium in Pekanbaru is Biomorphic Architecture. Biomorphic Architecture is part of architectural design that proposes all ideas taken from organic life, by form, system, or movement. Through the concept of Ocean Life Dynamics, the characteristics of building functions can be made as recreational facilities, conservation, and education about life under the sea.